IBD LIVE Series—Case 8: Treatment Options for Refractory Esophageal Crohn's Disease and Hidradenitis Suppurativa. Issue 10 (October 2017) - Iskandar, Heba; Greer, Julia B.; Krasinskas, Alyssa M.; Tinsley, Andrew T.; Koltun, Walter A.; Siegel, Corey A.; Levy, L. Campbell; Herfarth, Hans H.; Farraye, Francis A.; Binion, David G.; Rosh, Joel R.; Keljo, David J.; et al.
Abstract : Supplemental Digital Content is Available in the Text.